FROSTY, FREEZING AND SEVERE FREEZING DAYS AND THEIR SYNOPTIC IMPLICATIONS IN MAŁOPOLSKA, SOUTHERN POLAND, 1951–2000 - Bielec-Bąkowska, Zuzanna; Łupikasza, Ewa (Bulletin of Geography. Physical Geography Series, 2009)
This study discusses the occurrence of days with unique thermal characteristics for the period 1951–2000. The authors investigated longterm variability, probability of occurrence and synoptic conditions favourable to frosty (tmin≤0˚C ∧ tmax>0˚C), freezing (tmax<0˚C) and severe freezing (tmax<-10˚C) days at six stations in the southern part of Poland. The occurrence of frosty days is characterized by the highest diversity, both in spatial and temporal terms and these days depend on the landform to the highest degree. The number of freezing days ranged from 28–30 in the foothills of the Carpathians to 147 at 2000 m a.s.l. in the Tatra Mountains, with severe freezing days from ca. 2 to ca. 18 days respectively, though no distinct trends were noted in their long-term progression. The anticyclonic situations and air mass advection from the southern sector (frosty days), from the east, south-east and north (freezing and severe freezing days) were the most favourable for the days examined.